Early Blood Profile of C57BL/6 Mice Exposed to Chronic Unpredictable Stress - McDonald, Lindsay T.; Lopez, Marcelo F.; Helke, Kristi L.; McCrackin, M.A.; Cray, James J.; Becker, Howard C.; LaRue, Amanda C. (Frontiers in Psychiatry, 2019)
Physiological responses to psychological stressors are protective in acute fight or flight situations; however, there is increasing evidence suggesting detrimental impact of chronic psychological stress on disease. Chronic stress has been associated with inflammation, poor prognosis, increased morbidity and poor outcome in many diseases including atherosclerosis, cancer, and pulmonary disease. Given the systemic impact of stress, and the role of the hematopoietic system as a rapid responder to homeostatic insults, we hypothesized that early blood profile changes and biochemical alterations could be detected in a model of chronic stress. To test this hypothesis, a variation of the chronic unpredictable stress (CUS) model was employed. Following 10 days of CUS, C57BL/6 mice exhibited a chronic-stress associated corticosterone profile. Complete blood count (CBC) revealed mild normochromic, normocytic anemia, reduced monocyte and lymphocyte count. Serum analysis demonstrated hypoferremia with unchanged total iron binding capacity and serum ferritin levels. These findings are consistent with clinical diagnostic parameters for anemia of chronic disease and indicate that CUS results in significant changes in blood and serum biochemical profile in C57BL/6 mice. These studies identify early changes in blood parameters in response to CUS and identify hematopoietic and biochemical alterations that are often associated with increased morbidity in patients experiencing chronic stress-associated mental health disease.